PENGARUH CR DAN DER TERHADAP ROA PADA PT. SELAMAT SEMPURNA Tbk PERIODE 2010-2019 - Anisa, Sella Putri; Priyanto, Aria Aji (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.01.TAHUN.2022DO - 10.24843/EEB.2022.v11.i01.p06, 2022)
This research is in order to determine the influence of current ratio and debt to equity ratio on return on assets in the parts industry, namely PT. Selamat Sempurna Tbk period 2010-2019. The methods used in research are descriptively associative with quantitative approaches. The data analysis techniques used are financial ratio analysis, descriptive statistical analysis, statistical analysis through SPSS calculation stages using IBM SPSS version 25 (classic assumption test: normality test, multicolinearity test, heteroskedastisity test, autocorrelation test), simple linear regression test, multiple linear regression test, determination coefficient test and hypothesis test (t partial test and F simultaneous test). The results of this study showed that the Current Ratio (CR) and Debt to Equity Ratio (DER) simultaneously have a significant effect on Return On Asset (ROA) in PT. Selamat Sempurna Tbk. Partially available from the results of the t test that shows that the Current Ratio (CR) has a significant effect on Return On Asset (ROA) and Debt to Equity Ratio (DER) partially significantly affects Return On Asset (ROA).